La germinación de Sesbania emerus (Fabaceae): efecto de la inmersión en ácido sulfúrico - Guerrero, Maritza (Universidad de Costa Rica, 1994)
Seeds of Sesbania emerus harvested yearly ( 1989- 1992) were stored at 21 °C until 1992, when this experiment was done by separating brown and gray seeds. Immersion treatments with and without sulfuric acid for 20 min were carried out to interrupt seed dormancy. Gray seeds had higher germination values when treated with acid; on the contrary, no effect was noticed in brown seeds. Hipocotyl length and seedling dry weight were useful in determining vigor, except in brown seeds treated with acid, that show no decreseasing values with age